The effectiveness of the categories of protected areas in containing deforestation in the legal Amazon - Jorge Luis Gavina Pereira; Leandro Valle Ferreira (Boletim de Geografia, 2021)
One of the greatest global threats to biodiversity is habitat loss. In the 20th century, deforestation increased in the tropical domain, the most biodiverse area on the planet. The main strategy in the protection of natural habitats has been the creation of protected areas. One of the ways to assess the effectiveness of protected areas is by monitoring the original coverage. This article aimed to compare deforestation between categories of protected areas and a sample of unprotected areas of Legal Amazon in 2017. It was found that 45.2% of the Legal Amazon territory is in protected areas: 23.0% in indigenous lands, 7.7% in full protection conservation units, and 14.5% in sustainable use conservation units. It was also verified that 20% of the forest areas of the Legal Amazon had been deforested until 2017. Statistical analyses of deforestation values led to the formation of two sets. Set 1, effective in containing deforestation: indigenous lands (11.4% deforested); full protection conservation units (16.9% deforested); sustainable use conservation units, category 1 - Sustainable Development Reserve, Extractive Reserve and Government Forest (10.4% deforested). Set 2, without effectivity in containing deforestation: sustainable use conservation units, category 2 - Environmental Protection Area, Area of Relevant Ecological Interest and Private Natural Heritage Reserve (35.8% deforested); Non-Protected Area (38.0% deforested). In the effective protection of biodiversity and ecosystem services in the Legal Amazon, it is recommended to create full protection conservation units. Alternately, sustainable use conservation units, category 1 (public lands), or indigenous territories should be created because they are essential for conserving the sociocultural diversity of the Amazon.